2023
DOI: 10.1177/03009858231189205
|View full text |Cite
|
Sign up to set email alerts
|

Automated diagnosis of 7 canine skin tumors using machine learning on H&E-stained whole slide images

Abstract: Microscopic evaluation of hematoxylin and eosin-stained slides is still the diagnostic gold standard for a variety of diseases, including neoplasms. Nevertheless, intra- and interrater variability are well documented among pathologists. So far, computer assistance via automated image analysis has shown potential to support pathologists in improving accuracy and reproducibility of quantitative tasks. In this proof of principle study, we describe a machine-learning-based algorithm for the automated diagnosis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Deep learning-based tools, like nuclear morphometry algorithms, have been increasingly investigated for numerous diagnostic/prognostic tasks in veterinary and human pathology in the detection [ 47 , 48 ], classification [ 24 , 49 , 50 , 51 ], and grading of tumors [ 52 , 53 ]. These studies have proposed different ways for algorithms to be implemented into the diagnostic workflow (fully automated and computer-assisted diagnosis).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Deep learning-based tools, like nuclear morphometry algorithms, have been increasingly investigated for numerous diagnostic/prognostic tasks in veterinary and human pathology in the detection [ 47 , 48 ], classification [ 24 , 49 , 50 , 51 ], and grading of tumors [ 52 , 53 ]. These studies have proposed different ways for algorithms to be implemented into the diagnostic workflow (fully automated and computer-assisted diagnosis).…”
Section: Discussionmentioning
confidence: 99%
“…The current approach for assessing nuclear pleomorphism in cPC, following the methods of the 1997 grading system [ 7 ], is the categorical estimation into three classes based on the variation in nuclear size (anisokaryosis) and shape irregularity. Nuclear pleomorphism estimates by pathologists are considered to be limited by low reproducibility, as has been shown for canine mammary carcinoma [ 22 , 23 ] and canine cutaneous mast cell tumors [ 24 ] and is suspected for cPC.…”
Section: Introductionmentioning
confidence: 99%
“…However, more recently, genotype–phenotype correlation investigations have been performed as pan-cancer studies wherein an extensive range of genetic alterations are considered [ 133 , 134 , 143 ]. In veterinary oncology, investigations of deep learning-based tumour histology are starting to be performed on canine tumours, wherein artificial intelligence (AI)-based methods are using digitized whole-slide images (WSIs) to make pathological diagnoses, such as diagnosing canine skin tumours (of seven different types) [ 144 , 145 ] and canine osteosarcoma (where the AI program was able to identify specific histologic subtypes that may have prognostic value) [ 146 ]. However, to date, there has only been one genotype–phenotype correlation study in canines; it was recently shown that deep learning using a commercial AI histology software could detect the BRAF p.V595E mutation on HE-stained canine bladder cancer tissue sections ( Figure 9 ), with a sensitivity of 89% [ 147 ].…”
Section: Emerging Fields For Genetic Investigations Of Canine Tumoursmentioning
confidence: 99%